ANALISIS GAYA KEPEMIMPINAN OTOKRATIS DAN TINGKAT KEPUASAN KERJA PADA KINERJA KARYAWAN PT MITRA KONSINDO ABADI - Digma Lailil Al Kautsarrani; Diah Ayu Sanggarwati (PUTRA JAWA PUBLISHER, 2024)
Leadership style and job satisfaction levels play crucial roles in determining employee performance across various organizations. PT Mitra Konsindo Abadi, a growing company in the industrial sector, is also influenced by these factors. However, limited research has explored the relationship between autocratic leadership style, job satisfaction, and employee performance within this company. This study employed a qualitative approach, collecting data through surveys distributed to employees in various departments of PT Mitra Konsindo Abadi. The observed variables included autocratic leadership style, job satisfaction levels, and employee performance. The primary objective of this study was to analyze the impact of autocratic leadership style and job satisfaction levels on employee performance at PT Mitra Konsindo Abadi. Additionally, this study aimed to provide insights for company management to enhance leadership strategies and job satisfaction, thereby improving organizational performance. The results of the analysis indicate that an autocratic leadership style can increase employee job satisfaction, which in turn enhances employee performance. These findings underscore the significance of the leader's role in fostering a work environment that motivates job satisfaction and ultimately contributes to overall organizational performance.